ACCOUNTING INFORMATION VALUE RELEVANCE, FINANCIAL DISTRESS, AND STOCK PRICE BEHAVIOR: EMPIRICAL EVIDENCE FROM INDONESIAN LISTED BANKS - Resvi Noprianti; Holiawati; Ani Kusumaningsih (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the effect of the value relevance of accounting information, which is proxied by earnings, book value, and cash flows, as well as financial distress, on stock prices of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The fluctuations in stock prices in the post-pandemic period and differences in financial performance among banks motivated the need to re-examine the role of accounting information and financial distress in influencing firm value in the capital market. This research employs a quantitative approach using multiple linear regression analysis. The data used are secondary data consisting of annual financial statements and stock price data obtained from the official IDX website and published company reports. The sample was selected using a purposive sampling method based on predetermined criteria. The results show that earnings have a significant effect on stock prices, indicating that profitability information remains a key consideration for investors in assessing a company’s prospects. Book value is also found to have a significant effect on stock prices, suggesting that equity position is perceived by the market as an important indicator of a firm’s fundamental value. Meanwhile, cash flows do not have a significant effect on stock prices, implying that investors in the banking sector tend to place greater emphasis on accrual-based indicators than on cash-based indicators. Financial distress has a negative and significant effect on stock prices, meaning that higher levels of financial pressure reduce investor confidence, which in turn leads to a decline in stock prices. These findings reinforce signaling theory, which states that financial information disclosed by companies provides important signals for investors in making investment decisions.